2013
DOI: 10.1182/blood-2013-05-499384
|View full text |Cite
|
Sign up to set email alerts
|

Putting polyphosphates to the test: evidence against platelet-induced activation of factor XII

Abstract: Key Points• Coagulation factor XII is not activated by platelets.The recent claim that stimulated platelets activate the intrinsic pathway of coagulation by the release of polyphosphates has been considered a breakthrough in hemostasis research. In little more than 3 years, the original publication by Müller et al has been cited >100 times. However, none of the citing articles has sought to independently validate this potentially paradigm-shifting concept. To this end, we performed extensive experimentation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 32 publications
0
41
0
1
Order By: Relevance
“…PolyP can activate extracellular receptors (Dinarvand et al, 2014), modulate the excitability of neurons (Stotz et al, 2014) and protect cells from amyloid toxicity (Cremers et al, 2016). Although at times controversial (Faxalv et al, 2013), these findings have boosted interest in the polyP metabolism of eukaryotes. Further exploration of the role of acidocalcisomes and polyphosphates is hampered by our incomplete knowledge of the enzyme systems involved in polyP metabolism, even in the simple model organism Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…PolyP can activate extracellular receptors (Dinarvand et al, 2014), modulate the excitability of neurons (Stotz et al, 2014) and protect cells from amyloid toxicity (Cremers et al, 2016). Although at times controversial (Faxalv et al, 2013), these findings have boosted interest in the polyP metabolism of eukaryotes. Further exploration of the role of acidocalcisomes and polyphosphates is hampered by our incomplete knowledge of the enzyme systems involved in polyP metabolism, even in the simple model organism Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that platelet-derived polyphosphate promotes blood coagulation (5,6). However, the effects obtained when adding synthetic polyphosphate have been conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, studies have indicated that long chain polyphosphate (>45 phosphate units) may induce thrombosis and infection, linked with the activation of coagulation factor XII (FXII), via a bradykinin-dependent mechanism (5-7). However, Faxälv et al found that polyphosphate released from platelets did not activate FXII (5), and the relationship between synthetic polyphosphate, platelets and coagulation remains unclear. Therefore, the present study explored the effect of industrially synthesized polyphosphate on hemostasis and coagulation in a clinical laboratory setting and investigated the potential underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Datos recientes han cuestionado la validez de los estudios con los polifosfatos, fallando al reproducir resultados previos (16) .…”
Section: Papel Del Fxii In Vivounclassified